Design and experiment of a double-row self-propelled wheat plot planter - Feng, Yamei; Deng, Shidong; Cheng, Xiupei; Sui, Shuntao; Zhang, Xiangcai; Wei, Zhongcai; Wang, Xianliang (International Journal of Agricultural and Biological Engineering, 2026)
To address the challenges associated with the complex structure, poor sowing uniformity, and limited automation in plot breeding machinery, a double-row self-propelled wheat plot planter was designed, and an electronic control system was developed to manage plot seeding operations. This machine comprises the double-cone combined compartment tray-type seed-metering device, ditching and compacting device, self-propelled chassis device and electronic control system, which can complete the operation of ditching, seeding, and suppressing at one time. The electronic control system is centered around the STM32. The main method is to measure and control the operating speed of the seeder, then calculate the actual forward distance of the machine, and achieve automatic seed dropping in plots, fixed-length seeding, and control of the seed metering rotation speed. The optimization of the PID speed closed-loop feedback control algorithm, which precisely matches the rotational speed of the seed metering device with the operating speed of implement across different plot lengths, ensures accurate fixed-length seeding. The results of the soil trough test indicate that at an operating speed of 5 km/h and with the theoretical sowing length set to 2-8 m, the average control accuracy of actual plot sowing length exceeds 94%, and the variability coefficient of seeding depth is less than 10%. When the operating speed of seeder is 3-5 km/h, the coefficient of variation for seeding uniformity ranges from 26.18%-36.71%, remaining below 45%, thereby meeting the agronomic requirements for wheat plot seeding. The results of this study can serve as a reference for the design and optimization of wheat plot breeding trial equipment. Keywords: wheat plot planter, self-propelled, seeding control, plot experiment DOI: 10.25165/j.ijabe.20261901.9753 Citation: Feng Y M, Deng S D, Cheng X P, Sui S T, Zhang X C, Wei Z C, et al. Design and experiment of a double-row self-propelled wheat plot planter. Int J Agric & Biol Eng, 2026; 19(1): 132–142.